Cold start of proton exchange membrane fuel cell. (January 2018) - Luo, Yueqi; Jiao, Kui
Abstract: In this review, "cold start" is defined as the startup of proton exchange membrane (PEM) fuel cells from subfreezing temperatures. Problems occurring during the cold start pose some of the remaining barriers to commercial applications of PEM fuel cells in transportation, stationary, auxiliary and portable systems. Fundamental studies of transport phenomena are critical to a better understanding of the mechanisms of cold start and offer ultimate solutions to resolving cold-start issues. In this review, experimental studies are discussed, focusing on output performance degradation, water and ice visualization, and component damages during a cold start. Analytical, numerical, and microscopic models and their results are also discussed. One of the emphases is on transport phenomena relevant to cold starts, including supercooling, phase change and transport of water in the membrane, catalyst layer, microporous layer, and gas diffusion layer. Another emphasis is placed on the strategies utilized to optimize cold-start processes for improved performance. The strategies include material designs of the components, cell/stack structures, and startup mode/load controls. It is shown that all of the effective strategies to mitigating cold-start problems derive from a basic understanding of the transport mechanisms during a cold start. It is also suggested that future models for this problem should place a great deal of attention in supercooling phenomena and water phase-change and transport in multilayer porous media. Lastly, more advanced experimental methods, such as real-time water/ice visualization and cryogenic microscopy, are needed to validate emerging theories and models.